Source Identification of brGDGTs in the Surface Sediments of the East China Sea - Wang, Yipeng; Yang, Jialei; Wang, Guichen; Zhang, Yinyi; Zhang, Rui; Li, Tiegang; Russell, James; Wang, Jiayue; Wang, Xinling; Zhang, Fan; Song, Yuehua; Yu, Xiaoxiao; et al. (Frontiers in Earth Science, 2022)
Branched glycerol dialkyl glycerol tetraethers (brGDGTs) are components of bacterial membranes, that are widely used in paleoenvironmental reconstruction in global terrestrial soils and marine sediments. However, the sources of brGDGTs in marine sediments remain unresolved and controversial, which complicates their application in paleoenvironmental reconstruction. In this study, we reported the spatial distribution of brGDGTs and their related indicators in surface sediments from the East China Sea (ECS). MBTʹ 5ME values in sediments of the ECS are distinct compared with those in the catchment soils, suggesting marine in situ production of brGDGTs. Therefore, we also examined the existence of marine in-situ brGDGTs, and quantitatively determined the contributions of terrestrial and in situ production of brGDGTs. This study reported mixed sources, soil-derived brGDGTs were dominant, and marine in-situ brGDGTs were overprinted. In especially, there were predominantly marine in-situ brGDGTs in the outer shelf due to the weak riverine transportation, and were characterized by high #Ringstetra and IIIa/IIa.